2002
DOI: 10.1097/00001756-200201210-00028
|View full text |Cite
|
Sign up to set email alerts
|

The acute effects of exposure to the electromagnetic field emitted by mobile phones on human attention

Abstract: The aim of our study was to investigate the effects of acute mobile phone exposure on a range of tasks which tapped capacity and processing speed within the attentional system. Thirty-eight healthy volunteers were randomly assigned to either an experimental group which was exposed to a connected mobile phone or a control group in which the mobile phone was switched off. Subjects remained blind to mobile phone status throughout duration of study. The experimental group were exposed to an electromagnetic field e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
94
1
3

Year Published

2003
2003
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(102 citation statements)
references
References 19 publications
4
94
1
3
Order By: Relevance
“…A large number of behavioral and electrophysiological studies have been conducted but with inconsistent results (see Kwon and Hämäläinen, 2011, for a review). Earlier behavioral studies, for example, reported faster response speed in attention or working memory tasks (Preece et al, 1999;Koivisto et al, 2000a, b;Edelstyn and Oldershaw, 2002), but later more stringent studies (e.g., with corrections for multiple comparisons) failed to replicate such findings. Results of electroencephalography studies have also been contradictory particularly in the a band: some studies reported increased a activity (Croft et al, 2002(Croft et al, , 2008Curcio et al, 2005;Regel et al, 2007), while others found no such effects (Röschke and Mann, 1997;Hietanen et al, 2000;Perentos et al, 2007;Kleinlogel et al, 2008).…”
Section: Introductionmentioning
confidence: 98%
“…A large number of behavioral and electrophysiological studies have been conducted but with inconsistent results (see Kwon and Hämäläinen, 2011, for a review). Earlier behavioral studies, for example, reported faster response speed in attention or working memory tasks (Preece et al, 1999;Koivisto et al, 2000a, b;Edelstyn and Oldershaw, 2002), but later more stringent studies (e.g., with corrections for multiple comparisons) failed to replicate such findings. Results of electroencephalography studies have also been contradictory particularly in the a band: some studies reported increased a activity (Croft et al, 2002(Croft et al, , 2008Curcio et al, 2005;Regel et al, 2007), while others found no such effects (Röschke and Mann, 1997;Hietanen et al, 2000;Perentos et al, 2007;Kleinlogel et al, 2008).…”
Section: Introductionmentioning
confidence: 98%
“…Several studies have suggested that an electromagnetic field (EMF) emitted by a mobile phone can interact with brain activity and behavior [Eulitz et al, 1998;Freude et al, 1998Freude et al, , 2000Hamblin and Wood, 2002;Preece et al, 1999;Koivisto et al, 2000a,b;Krause et al, 2000a,b;Edelstyn and Oldershaw, 2001;Lee et al, 2001].…”
Section: Introductionmentioning
confidence: 99%
“…However, there have been several reports of physical abnormalities occurring because of electromagnetic waves emitted by such electronic devices [13]- [20]. In addition, the incidence of adverse biological effects due to electromagnetic waves may be increasing.…”
Section: Discussionmentioning
confidence: 99%